Comparative analysis of 1152 African-American and European-American men with prostate cancer identifies distinct genomic and immunological differences - Walter Rayford (Nature Portfolio, 2021)
Walter Rayford, Alp Tuna Beksac et al. investigated gene expression alterations in African-American and European-American men who underwent radical prostatectomy for prostate cancer. The observed differences include higher expression of inflammation genes and lower expression of mismatch repair genes in African-American men.